THEORETICAL STUDY OF VARIOUS SOLVENTS EFFECT ON 5-FLUOROURACIL-VITAMIN B3 COMPLEX USING PCM METHOD - Khanmohammadi, Azadeh; Mohammadi, Marziyeh (Journal of the Chilean Chemical Society, 2019)
In this article, a detailed study of the solvent effects on the stability order, binding energy and hydrogen bond strength in 5-Fluorouracil-Vitamin B3 (FU–VB) complex is performed using M05-2X method with 6-311++G(d,p) basis set. Based on the average of the calculated H-bond energies, the H-bond strength of FU-VB complex in gas phase is more than solution phase. The binding energy in solution phase is also lower than the gas phase. Therefore, the stability of the studied complex increases in solution phase with respect to the gas phase. Furthermore, the topological properties of the electron density distribution are analyzed in term of the Bader Quantum Theory of “Atoms in Molecules” (QTAIM). The natural bond orbital (NBO) method is also applied to get a more precise insight into the nature of intermolecular interactions. Finally, the solvent effect on the frontier molecular orbital energies (HOMO and LUMO), chemical potential and hardness of FU–VB complex is investigated.